Airborne Microbial Quality Assessment in the Educational Buildings during the COVID-19 Pandemic - Muhammad Asril; Salsabila Sugiarto; Alfian Zurfi (Civil Engineering Journal, 2023)
Rooms with pollutants have a poor impact of 2-5 times greater than outdoors. The lecture hall had the potential to experience a decrease in air quality. This study was conducted to assess microbiological air quality in the general lecture building I Institut Teknologi Sumatra, Lampung, Indonesia, during the COVID-19 pandemic and its relationship with environmental conditions. This study was conducted using a settling sampling technique to count the number of bacteria and fungi in the air. Samples were collected twice daily for five working days. The results showed that the highest concentrations of bacteria and fungi were found at the wifi corner location, at 36.7–1237.2 CFU/m3 and 225.4–1431.2 CFU/m3, respectively. The highest average concentrations of bacteria and fungi at the wifi corner location were found in the afternoon at 479.1 ± 438.1 CFU/m3 and 800 ± 548.4 CFU/m3, respectively. The three locations did not meet the standards of room suitability for humans with immunodeficiencies based on the ACGIH. The location of the wifi corner did not meet the standards of the Minister of Manpower of the Republic of Indonesia No. 5 of 2018 and the WHO regarding microbial standards in the room. The highest value of the Global Microbial Contamination Index (GIMC/m3) was found in the wifi corner (G4: ≥2000 – ≤4000), which is closely related to population density and ventilation. Environmental factors influence the density of bacteria and fungi at the sampling sites. The relative humidity strongly influenced the concentration of fungi. In addition to relative humidity, bacterial density is also affected by light intensity and the number of people. This indicates that despite restrictions on activities during the COVID-19 pandemic, the room at GKU 1 did not meet the eligibility requirements for students with immune disorders. Doi: 10.28991/CEJ-2023-09-01-09 Full Text: PDF